Konvergensi Geographic Information System dalam Manajemen Kesehatan Unit Pelaksana Teknis Daerah: Indonesia - Hakim, Bela Pitria; Permatasari, Intan; Sjafrizal, Teddy; Anugraha, Rino Andias (Jurnal Abdimas Madani dan Lestari (JAMALI), 2025)
Improving the quality of health management is a fundamental basis for enhancing community well-being. A primary challenge faced by PUSKESMAS is the suboptimal management of health data, which impedes program monitoring and response to diseases. The implementation of Geographic Information System (GIS) technology at UPTD PUSKESMAS Urug, Kawalu District, Tasikmalaya City, as a community service output from Telkom University, aims to address this issue. GIS enables spatial mapping of community health data, such as patient locations and disease distribution, facilitating better analysis and decision-making. The development of this GIS application involved initial data collection, system design, and Focus Group Discussions with PUSKESMAS staff. The results show improvements in data integration, spatial visualization, and decision-making efficiency, particularly in mapping non-communicable diseases. The system’s socialization to users has received positive feedback and enhanced health resource management. The ease of data updating is a notable advantage in its operation. Further development is recommended to include various other health aspects to maximize the benefits of this technology for the community. Ultimately, the implementation of GIS at PUSKESMAS Urug holds significant potential to improve the quality and responsiveness of health services and could serve as a reference for other PUSKESMAS.